A Strategy toward New Low‐Dimensional Hybrid Halide Perovskites with Anionic Spacers. Issue 6 (15th January 2019) - Zhao, Yizhou; Zhang, Siyu; Lu, Yue; Lan, Shangui; Zhu, Cheng; Xiao, Jiawen; Zai, Huachao; Sui, Manling; Li, Dehui; Zhou, Huanping; Li, Yujing; Chen, Qi
Abstract: The low‐dimensional halide perovskites have received enormous attention due to their unique photovoltaic and optoelectronic performances. Periodic spacers are used to inhibit the growth of 3D perovskite and fabricate a 2D counterpart with layered structure, mostly based on organic/inorganic cations. Herein, by introducing organic anions (e.g., pentanedioic acid (PDA) and hexanedioic acid (HDA) simultaneously), leaf‐shaped (Cs3 Pb2 Br5 )2 (PDA–HDA) microplates with low‐dimensional structure are synthesized. They also exhibit significant photoluminescence (PL) centered at 540 nm with a narrow emission peak. The synthesis of single crystals of Pb(PDA) and Pb(HDA) allows to further clarify the crystal structure of (Cs3 Pb2 Br5 )2 (PDA–HDA) perovskite and its structural evolution mechanism. Moreover, the cooperative introduction of dicarboxylic acid pairs with appropriate lengths is thermodynamically favored for the low‐dimensional perovskite crystallization. The temperature‐dependent PL indicates a V‐shaped Stokes shift with elevated temperature that could be associated with the localization of excitons in the inorganic layers between organic dicarboxylic acid molecules. This work demonstrates low‐dimensional halide perovskite with anionic spacers, which also opens up a new approach to the growth of low‐dimensional organic–inorganic hybrid perovskite crystals. Abstract : The employment of anions as spacers to synthesize a new 2D hybrid perovskite family is reported. Moreover, this new class of 2D Cs‐based halide perovskites exhibits novel morphology and strong photoluminescence, which is potentially feasible for optoelectronic applications.